Pengaruh Destination Image dan Kunjungan Wisatawan terhadap Lokasi Wisata Baru - Setyorini, Alberta Dwi; Sugiharto, Totok (E-Jurnal Akuntansi, 2021)
Bali has fascinating many tourists from all over the world to visit and Nusa Penida is an island located in the southern part of Bali that requires a speedboat to get there, and Penida Beach Club is a new tourist location.  The purpose of this study was to determine whether there is an influence between destination image and tourist visits on new tourist sites. The test was carried out with SPSS - multiple linear regression in order to make it easier for the author to process data and the results of the calculation can be concluded that 40.9% of destination images and tourist visits affect new tourist sites, while 59.1% are influenced by other variables not included in the study, and simultaneously test obtained 0.009 <0.05 which can be concluded that the destination image and tourist visits significantly affect new tourist locations, also from both hypothesis the tourist visit to the new location has a significant impact than the destination image to the new location. Keywords: Destination Image; Tourist Visits; New Location.